Molecular dynamics simulation of displacement cascades in α-Fe: A critical review - Malerba, L. (Journal of nuclear materials, 2006)
Little more than 10 years ago the first paper on molecular dynamics (MD) simulation of displacement cascades in α-Fe using a many-body potential was published by Calder and Bacon [J. Nucl. Mater. 207 (1993) 25]. Since then, a large body of literature data has been produced on the subject using different interatomic potentials. In this review, most of the available data from the literature are compared in order to discuss to what extent they are consistent. It is found that, while the number of Frenkel pairs versus cascade energy is essentially the same for most potentials, yielding a defect production efficiency in agreement with experimental estimates, differences exist concerning the point-defect clustered fractions. In the case of self-interstitial atoms (SIA), the criterion used to define clusters is largely responsible for the discrepancies, but differences also exist as a consequence of the different interatomic potentials. Too few data have been published concerning vacancy clusters to draw definitive conclusions. The existing differences do not correlate in any explicit way with the description that the interatomic potential gives of point-defects and their mobility.